KOMUNIKASI INTERPERSONAL ORANGTUA PADA GAMERS DALAM MENGATASI KECANDUAN GAME ONLINE MOBILE LEGENDS DI DESA GARUNTUNGAN KECAMATAN KINDANG KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The main problems in this study are divided into two: 1) Interpersonal Communication of Parents to Gamers in overcoming Mobile Legends Online Game Addiction in Garuntungan Village, Kindang District, Bulukumba Regency. 2) Parents' Barriers and Solutions in Communication to Overcome Mobile Legends Online Game Addiction. This type of research uses descriptive qualitative research with a research approach is an interpersonal communication approach—data collection using observation techniques, interviews, and documentation. Data sources were obtained from parents and children addicted to online games. Data processing techniques are carried out by data reduction, data presentation, as well as conclusion drawing and verification. The results of this study show the characteristics of interpersonal communication. Namely, openness (parents and children express all their thoughts openly without fear and shame to say them), empathy (parents' attitudes that care about their children), and supportive attitudes (parents provide support for their children to stop or reduce their activities, namely playing mobile legends online games). Parental obstacles in overcoming addiction to mobile legends online games are 1) Personal obstacles occur because the child does not listen to what parents say and only focuses more on the game. 2) Fun with their world, children only focus on playing online games on their cellphones without caring about what is around them. The solution is to give them a job so that they can forget the game and also put their children in boarding schools so they can't hold cell phones.